Toxicidade reprodutiva da semente de neem (azadirachta indica A. Juss.) Em codorna (coturnix coturnix japônica linnaeus, 1758) macho: Características seminais, estudo histopatológico e Histomorfométrico do parênquima testicular - Góis, Rayr Cezar de Souza (Universidade Federal Rural do Semi-Árido, 2018)
The Neem (Azadirachta indica A. Juss.) is a plant that was introduced in Brazil with the aim to be utilized in the development of natural insecticid, that could be used in the crops . This plant has several activities already described in the literature: bactericid, fungicid, antiinflammatory, hepatoproctetive, anti-diabetic, vermifuge, carrapaticida and spermicide, besides causing negative effects on the reproduction of insects and mamals. However, this negative action in birds, hasn't been described in the literature. Thus, the present work aims to evaluate reproductive toxity of neem seed in birds using the quail as an exprimental model. Therefore, 50 quails (Coturnix coturnix japônica Linnaeus, 1758) adult males will be distributed in five experimental groups: T1, T2, T3, T4 e T5, They will receive diet containing : 0, 5, 10, 20 and 40% of seed incorporated into the feed during 60 days. After the experimental period, the semen will be collected from the deferent duct of each bird for sperm analysis (concentration, mobility, vigour, viability, and morphology). To determine the biometric parameters, the testicles will be weighd on an analytical scale and measured ewith the aid of a digital caliper, obtaining valuesreferring to the weight, lenght and width of the righ and left testicle. Afterwards, The testicles will be fixed in bouin solution and submitted to the prepation of histological laminae, stained by Hematoxylin and Eosin (HE). The laminae will be evaluated by optical microscopy to study the histophatological alterations of the testicular parenchyma. The histological gashes also will be evaluated by testicular morphometric parameters: tunica albuginea thickness, seminiferous tubule diameter, and the germinal epithelial heigh. Statistical analysis will performed by SAS software (1999) and strudent's t-test with 5% (P < 0,05) of significance. The histolocal analysis revealed that the birds belonging to these groups presented degeneration of germinal epithelial cells. The histomorphometric measurements of the testicles showed that the T4 and T5 animals presented a significant increase ( P<0,01) in the average value of the tunic albuginea thickness, and a signicant reduced in the values of the seminiferous tubule diameter, and the high of the germinative epithelium in T4 and T5 . In the treatments mentioned there was significantly reduced of: average values of seminal volume, sperm concentration, sperm mobility, vigor and spermatical viability
Keywords: Alterações testiculares; Qualidade espermática; Aves; Intoxicação experimental; Neem; Testicular alterations; Spermatic quality; Birds; Experimental intoxication; Neem; CIENCIAS AGRARIAS::MEDICINA VETERINARIA